Penerapan Metode Storytelling untuk Meningkatkan Kemampuan Historical Imagination Siswa dalam Pembelajaran Sejarah (Penelitian Tindakan Kelas XI IPS 2 SMAN 7 BANDUNG) - Wulandari, Kristi; Kusmarni, Yani; Darmawan, Wawan (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2024)
This research is motivated by the complexity found by researchers in class XI IPS 2 of SMAN 7 Bandung, namely the ability of historical imagination that is low in students' ability to learn history. While this ability is important to help students imagine in reconstructing and explaining historical stories. The main objective of this research is to improve the ability of students' historical imagination in learning history. Indicators developed in this study are the results of research researchers who discuss about experts, namely the discussion of the idea of a chain script, the product of a serial story script, the discussion of the packaging of a serial script, and the making of storytelling. This class action research was carried out for two cycles where one cycle contained three actions using the Ebbut model which consisted of discussions about focus and initial planning (plan), action implementation (observation), observation (observation), implementation of the research process (reconnaissance), and reflection (reflection). The results showed an increase in the imagination of history in each cycle after applying the method of storytelling in learning history. This can be seen from the increase in the achievement of values in each indicator. Based on these data it can be concluded that the application of storytelling method can be an alternative to improve the ability of students' historical imagination in learning history at SMAN 7 Bandung.